2017
DOI: 10.3390/molecules22122024
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Preparative Separation of 10 Lignans from Justicia procumbens L. by High-Speed Counter-Current Chromatography

Abstract: Ten compounds, including three lignan glycosides and seven lignans, were purified from Justicia procumbens L. in 8 h using an efficient strategy based on high-speed counter-current chromatography (HSCCC). The two-phase solvent system composed of petroleum–ethyl acetate–methanol–H2O (1:0.7:1:0.7, v/v) was firstly employed to separate the crude extract (320 mg), from which 19.3 mg of justicidin B (f), 10.8 mg of justicidin A (g), 13.9 mg of 6′-hydroxyjusticidin C (h), 7.7 mg of justicidin E (i), 6.3 mg of lignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The selection of two-phase solvent system was based on the partition coefficient ( K ) of the three target compounds. The K values were determined by HPLC [ 15 ]; approximately 2 mg of crude extract was added to a test tube, and 2 mL of equilibrated two-phase solvent system was added. The test tube was shaken violently for several minutes to make the sample fully dissolve.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of two-phase solvent system was based on the partition coefficient ( K ) of the three target compounds. The K values were determined by HPLC [ 15 ]; approximately 2 mg of crude extract was added to a test tube, and 2 mL of equilibrated two-phase solvent system was added. The test tube was shaken violently for several minutes to make the sample fully dissolve.…”
Section: Methodsmentioning
confidence: 99%
“…A diphyllin isomer was annotated as justicidin H (also called 6 0hydroxyjusticidin B). 37 Justicidin H produced main fragments at m/z 363, 351, 337, 319, and 291. The fragment at m/z 363 was attributed to water loss followed by loss of CO 2 (m/z 319), while the fragment of m/z 351 resulted from a neutral loss of formaldehyde.…”
Section: Lignansmentioning
confidence: 99%
“…Previous studies have reported that J. procumbens is composed of various ingredients such as lignans, lignan glycosides, alkaloids, flavonoids, and triterpenes [ 15 ]. Lignans and lignan glycosides are major constituents of J. procumbens , which exhibits various pharmacological activities including anti-inflammatory, anti-tumor, anti-viral, anti-hepatitis, and anti-platelet aggregation [ 16 ]. In addition, the entire plant of J. procumbens has long been used as a herbal remedy for the treatment of fever, pain, cough, edema, jaundice, sore throat, urinary tract infection, and cancer [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%